P21 AGE–RELATED DIFFERENCES AND ASSOCIATED OUTCOMES OF S–ICD: INSIGHTS FROM A LARGE, EUROPEAN, MULTICENTER REGISTRY. (18th May 2022) - Schiavone, M; Gasperetti, A; Gulletta, S; Vogler, J; Fastenrath, F; Breitenstein, A; Laredo, M; Mitacchione, G; Palmisano, P; Compagnucci, P; Kaiser, L; Denora, M; et al.
Abstract: Background: The subcutaneous implantable cardioverter defibrillator (S–ICD) has become an alternative to transvenous ICDs (TV–ICD) in patients who do not need pacing. To date, there is little evidence directly comparing the rates of inappropriate shocks (IAS) in young vs old S–ICD recipients. Purpose: Aim of our study was to assess differences in device–related complications and inappropriate shocks (IS) between teenagers/young adults and adult recipients of a subcutabeous implantable cardioverter defibrillator (S–ICD) device. Methods: Two propensity–matched cohorts of teenagers + young adults (≤ 30–year–old) and adults (> 30–year–old) were retrieved from the ELISIR registry. The primary outcome was the comparison of the inappropriate shock (IAS) rate; complications, freedom from sustained ventricular arrhythmic events, overall and cardiovascular mortality were deemed secondary outcomes. Results: A total of 1491 patients were extracted from the ELISIR project. Teenagers + young adults represented 11.0% of the entire cohort. Two propensity–matched groups of 161 patients each were used for the analysis (Figure 1 ); median follow–up was 23.1 [13.2–40.5] months. 15.2% patients experienced inappropriate S–ICD shocks and 9.3% device related complications were observed with no age–related differences in IAS (16.1% vs 14.3%; p = 0.642) and complication rates (9.9% vs 8.7%; p = 0.701); Figure 2 shows a survival analysis from inappropriate shocks in the teen–ager/young adult cohort (red) and in the adult cohort (blue). At univariate analysis, young age was not associated with increased rates of IAS (HR 1.204 [0.675–2.148]: p = 0.529). At multivariate analysis (Figure 3 ), the use of SMART pass algorithm was associated to a strong reduction in IAS (aHR 0.292 [0.161–0.525]; p < 0.001), while ARVC was associated with higher rates of IAS (aHR 2.380 [1.205–4.697]; p = 0.012). Conclusion: In a large multicentered European registry of patients with S–ICD, 11.0% of all recipients were teenagers or young adults. The use of S–ICD in teenagers/young adults resulted safe and effective, and the rates of complications and IAS between teenagers/young adults and adults were not significantly different. The only predictor of increased IAS was a diagnosis of ARVC.